Pengaruh Work Environment Dan Work Stress Terhadap Kinerja Karyawan - Askhal, Mochammad Zidane (Universitas Negeri Surabaya, 2023)
In this modern era, the importance of managing quality and competent human resources (HR) is one of the determining factors for the success or failure of a company in achieving its goals. Work Stress and Work Environment are determinants of whether the employee performs well in PT. XYZ. The phenomenon of many employees feeling stress and the influence of the work environment is behind this study. This study used a quantitative type of research. The respondents in this study were employees of the marketing division at PT. XYZ, as many as 34 people were processed using linear regression with SPSS 22. The results showed that work stress and work environment affect performance. The research finds that both factors significantly influence performance. A positive work environment fosters harmonious relationships and meaningful contributions, while work stress negatively affects performance. Addressing these factors collectively enhances the potential for efficient work, leading to higher productivity and improved quality at PT. XYZ.